SYMBOLS, CHARISMA, AND RELIGIOUS AUTHORITY: POLITICAL COMMUNICATION STRATEGY OF ULAMA IN REGIONAL ELECTIONS - Din Fahmi Kamil; V. Rudy Handoko; Endang Indartuti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Moral support and political communication at the local level have a significant impact on the victory of regional head candidates in Tapal Kuda. This study aims to analyze the role of religious scholars in local political communication, the strategies used, and their impact on the results of the regional head elections. This study uses a qualitative approach with a case study method in two regions with strong religious cultures: Probolinggo, Bondowoso, Jember, and Situbondo Regencies. The results found Moral Endorsement, where religious scholars provide explicit support to certain candidates, often by linking the candidate's character to religious values. The dissemination of political messages through religious sermons, mass mobilization, religious scholars mobilizing their support base to attend campaigns and using religious networks to strengthen political support.